The Implementation Of The Teaching Strategy In Gymnastics In The Colleges And High Schools Of Porto-Novo : Cas Of Higth Schools Djegan-Kpevi, Cocotiers And Male : Difficulties and Prospects - AGBODJOGBE, D. BASILE; Ogueboule, Bachar M; ATTIKLEME, Kossivi; houndjenoukon, Elie (My University, 2018)
This study aims to analyze the implementation of the strategy of teaching by the pars by the teachers at the time of a sequence of class in gymnastics. constructivism of Vygotsky (1978) and situations of Brousseau (1986), it is a question of showing the various adaptations operated by the teachers in spite of the difficulties which they encounter at the time of the implementation of this strategy. framework reveals that during the execution of the tasks, the teachers invite the pupils to form small groups in which they responsabilize some of them having the control of the elements gymnic. learning. What could create psychological frustrations at the pupils? do not manage to find satisfaction because sometimes of the failures on the level of t order to check the attack of the objectives and the conformity of the indications of the tutor to the standard, the teacher does not cease making turns on the workshops. the teacher to appropriate all the of his role as a guide and supervisor
Keywords: Strategy; Teaching by Peers; Gymnastics